Do plantio à colheta: a ação do psicólogo e a escuta dos conflitos nas organizações - Silva, Regina Coeli Araujo da (2010)
The motivation for developing this study arose from a long history of working with various of Human Resources teams entered in companies. During this walk we could analyze, share and engage in numerous conflicts, which the parties involved, the workers, had misgivings about the organizational processes of various natures. This experience led us to observe that the psychological practices in companies seem to emphasize the aspects related to institutional objectives and management over the biopsychosocial aspects of the workers who demand. This realization prompted us to investigate the action of professional psychology in companies and discuss the clinical listens to deal with the conflicts that arise between workers. Specifically, we are interested in understanding the actions developed by these professionals and the demands that emerge from the conflicts experienced in the world of work. Another issue, with respect to the contribution of listening and clinical training in psychology to the interventional strategies adopted in response to suffering of the worker. Adds to reasons arising from our work experience with companies, studies and surveys conducted by several authors who have worked throughout the text, which served as a theoretical contribution to this dissertation. To understand the field to be investigated, there was a semistructured interview with seven professional psychology that have employment relationship at Human Resources of their respective companies, six from the private sector and public administration, all located in the metropolitan area Recife / PE. By analyzing the contents explained by thematic areas and the development of core meanings, narratives obtained enabled us to understand the action of psychologists in companies is characterized mainly by a speech and a listener grounded on institutional goals, aimed at operational and worker productivity. We also revealed that there are many challenges faced by practitioners, considering especially the condition that they, too, in the position of employees, a fact that favors the adoption of the organizational discourse of voluntary servitude and managerialism. It is intended that the results of this research can contribute to the formation of a critical and reflective in the professional organizations of psychologists in order to offer them subsidies to a listener focused on the real needs of employees who demand for their interventions. It is hoped also that this study can offer for these professionals, a better understanding of the conflicts that reveal themselves in the world of work, relating them to the possibilities of signification of the workers' suffering.